Advances in graphene oxide-based polymeric wound dressings for wound healing - Li, Shifeng; Wang, Jiao; Zhang, Hua; Zhang, Xin (Frontiers in Materials, 2025)
Conventional wound dressings can only provide basic protection for wounds and have limited ability to promote wound healing. Therefore, it is of great practical significance to develop new wound dressings with antibacterial, hemostatic, wound healing promotion, and good biocompatibility. Graphene oxide (GO), as a new type of nanomaterial, has received widespread attention in the fields of tissue engineering, bioimaging, biosensing, cancer therapy, and drug delivery. Due to unique physicochemical properties and multifunctionality of GO, polymers integrated with GO have the advantages of excellent antibacterial effect, good biocompatibility, significant wound healing promotion, and intelligent response, thus becoming new wound dressing materials with great potentials. This review systematically summaries the antibacterial, hemostatic, and angiogenic effects and mechanisms of GO. Then the research progress of GO as a core material combined with polymer compounds to form GO-based polymeric wound dressings is focused, followed by an in-depth discussion on their biocompatibility. Finally, this review further prospects the future research direction of GO-based polymeric wound dressings, with a view to providing ideas for their research and application.